2019
DOI: 10.1002/jor.24201
|View full text |Cite
|
Sign up to set email alerts
|

Volume change in infrapatellar fat pad is associated not with obesity but with cartilage degeneration

Abstract: Infrapatellar fat pad has been implicated in knee osteoarthritis. We examined whether infrapatellar fat pad volume is associated with quantitative cartilage changes using magnetic resonance imaging T1ρ mapping. Fifty‐eight knees of knee pain patients (19 men, 39 women, mean age 57.0 [range 29–85] years) who were conservatively managed and had >1 T1ρ mapping images taken over time were evaluated. We used three slices from the medial femoral and tibial cartilage; areas showing T1ρ values <130 ms and >50 ms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Higher BMI negatively correlated with the IPFP areas (r = − 0.161, P value = 0.018). Similarly, Masaki et al reported statistically significant negative correlation between IPFP volume and BMI (r = − 0.29; P < 0.001) [15]. While other results reported by Han et al found no significant association between IPFP area and BMI [14].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Higher BMI negatively correlated with the IPFP areas (r = − 0.161, P value = 0.018). Similarly, Masaki et al reported statistically significant negative correlation between IPFP volume and BMI (r = − 0.29; P < 0.001) [15]. While other results reported by Han et al found no significant association between IPFP area and BMI [14].…”
Section: Discussionmentioning
confidence: 85%
“…They stated that the lack of significant association between measures of body adiposity (SC fat, trunk fat) and the size of the IPFP might suggest that the IPFP size is not simply a marker of systemic obesity. Similarly, Masaki et al [15] stated that IPFP is maintained even in starved conditions where SC fat diminishes.…”
Section: Discussionmentioning
confidence: 91%
“…It is particularly important to estimate dimensions of Hoffa's fat pad because variations in its volume and thickness can result in degenerative changes of the knee joint, as seen for example in Osteoarthritis, reducing physical performance and consequently abilities to perform well in activities of daily living, becoming a cause of chronic disability [33].…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first step aiming toward this goal. Hence, as IPFP is now considered an early marker of OA incidence or progression [5][6][7][8][9] , being able to predict this tissue volume with serum biomarkers could enable a next step in which this information will be used to predict/discriminate OA progressors from non-progressors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that alteration in the infrapatellar fat pad (IPFP), an adipose tissue and the largest soft tissue structure in the knee joint 4 , is a potential early marker of OA disease incidence or progression [5][6][7][8][9] . Some inflammatory factors and adipokines produced by the IPFP have been identified as having a role in OA progression 10,11 .…”
mentioning
confidence: 99%